Analysis of Lecturers' Speech Disruption on the Teaching and Learning Process - Silitonga, Harpen; Sipayung, Kammer; Sidabutar, Usman (Universitas Pahlawan Tuanku Tambusai, 2026)
This study focuses on speech disruption in lecturers spoken discourse on the teaching and learning process, particularly in English language education through academic activity. The focus of this study is the analysis of types of speech disruption that occur in spoken discourse and the functional disorders realized in lecturers' speech through language production. The qualitative descriptive method in this study was designed with the aim of finding the types of speech disorders and the realization of their application functions in clause discourse. The findings show that repetitions amounted to 28.45% and revisions occurred to 28.45% as the dominant occurrences. Interjections followed 19.82%, silent pauses 28.45%, and filled pauses 10.35%. Segments of lexical, syntactic, semantic, or phonological morphological material amounted to 33% and periods of time when no phonation was performed during spoken discourse were 27%. The dominant occurrences based on the types and functions are cohesively related to language proficiency.